Integrasi Canva AI Sebagai Teknologi Artificial Intelligence Dalam Pembelajaran Desain Konten Digital Mahasiswa Pendidikan Islam Anak Usia Dini - K, Kisno.; Fatmawati, Nia (IJIGAEd: Indonesian Journal of Islamic Golden Age Education, 2025)
The development of Artificial Intelligence (AI) technology has encouraged learning transformation in universities, including in the field of Early Childhood Islamic Education. Students of the Early Childhood Islamic Education study program are not only required to have pedagogical competence and Islamic values, but also digital literacy skills and the ability to design creative and educational learning content. One of the AI-based technologies that has the potential to support Digital Content Design learning is Canva AI.  This study aims to conceptually examine the integration of Canva AI as an Artificial Intelligence technology in learning Digital Content Design for students of the Early Childhood Islamic Education study program at Universitas Islam Negeri Jurai Siwo Lampung. This research uses a qualitative approach with a type of conceptual research through literature studies on various relevant literature, both national and international journals. Data was analyzed using content analysis techniques to identify the roles, benefits, and pedagogical implications of using Canva AI in learning. The results show that Canva AI integration can support the development of creativity, digital literacy, and students' ability to design digital learning content that is appropriate to early childhood characteristics and nuanced with Islamic values. In addition, the use of Canva AI is in line with the technology-based learning paradigm and Outcome-Based Education (OBE) in universities. This article is expected to be a theoretical reference for lecturers and study program managers in developing AI-based Digital Content Design learning in the Islamic higher education environment.